Syntax Language Skill in Children with Down Syndrom: A Systematic Review - Purnaningrum, Windiarti Dwi; Sudrajad, Kiyat (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Down syndrome (SD) is the most common genetic disorder and the easiest to identify. SD or better known as the genetic disorder trisomy, where there is an extra chromosome on chromosome 21. Objectives: Analyzing syntax abilities in Down Syndrome children and learning materials in writing scientific research as well as providing additional information regarding syntax abilities in Down Syndrome children. Methods: The research carried out is a systematic review research. This research uses data from previous research. A quantitative systematic review combines findings from various independent studies, and produces a statistical summary of those findings (Last, 2001 in Murti, 2018). Results: Down syndrome children show conditions of intellectual problems that are continuous with language problems. Where cognitive abilities are the main capital in communication. Conclusion: Syntax communication abilities create core impairments in the narratives of children with Down syndrome. Syntax difficulties and deficits in global executive function when compared with children with other typical development.. Keywords: Syntax Language, Down syndrome, Systematic review